Utility of recorded guided imagery and relaxing music in reducing patient pain and anxiety, and surgeon anxiety, during cutaneous surgical procedures: A single-blinded randomized controlled trial - Alam, Murad; Roongpisuthipong, Wanjarus; Kim, Natalie A.; Goyal, Amita; Swary, Jillian H.; Brindise, Renata T.; Iyengar, Sanjana; Pace, Natalie; West, Dennis P.; Polavarapu, Mahesh; Yoo, Simon (Journal of the American Academy of Dermatology, 2016)
Guided imagery and music can reportedly reduce pain and anxiety during surgery, but no comparative study has been performed for cutaneous surgery to our knowledge. We sought to determine whether short-contact recorded guided imagery or relaxing music could reduce patient pain and anxiety, and surgeon anxiety, during cutaneous surgical procedures. Subjects were adults undergoing excisional surgery for basal and squamous cell carcinoma. Randomization was to guided imagery (n = 50), relaxing music (n = 54), or control group (n = 51). Primary outcomes were pain and anxiety measured using visual analog scale and 6-item short-form of the State-Trait Anxiety Inventory, respectively. Secondary outcomes were anxiety of surgeons measured by the 6-item short-form of the State-Trait Anxiety Inventory and physical stress of patients conveyed by vital signs, respectively. There were no significant differences in subjects' pain, anxiety, blood pressure, and pulse rate across groups. In the recorded guided imagery and the relaxing music group, surgeon anxiety was significantly lower than in the control group. Patients could not be blinded. Short-contact recorded guided imagery and relaxing music appear not to reduce patient pain and anxiety during excisional procedures under local anesthetic. However, surgeon anxiety may be reduced when patients are listening to such recordings.